2015
DOI: 10.1007/978-3-319-17344-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches to Identification of Aggregation Sites and the Mechanism of Amyloid Growth

Abstract: This chapter describes computational approaches to study amyloid formation. The first part addresses identification of potential amyloidogenic regions in the amino acid sequences of proteins and peptides. Next, we discuss nucleation and aggregation sites in protein folding and misfolding. The last part describes up-to-date kinetic models of amyloid fibrils formation. Numerous studies show that protein misfolding is initiated by specific amino acid segments with high amyloid-forming propensity. The ability to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…One of the outcomes of these efforts is the so-called “short-stretch hypothesis”, which postulates that a short amino acid stretch could provide most of the driving force needed to trigger the self-assembly of a protein into an amyloid 46 47 48 . This observation has pushed the development of over twenty different algorithms, aimed to identify these sequence stretches in disease-linked polypeptides 49 50 , whose predictions have been experimentally validated in many instances. Indeed, compounds blocking these regions have been shown to successfully interfere with entire protein aggregation reactions 51 and conversely mutations that increase the amyloid propensity of these stretches usually exacerbate full-length protein deposition 52 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the outcomes of these efforts is the so-called “short-stretch hypothesis”, which postulates that a short amino acid stretch could provide most of the driving force needed to trigger the self-assembly of a protein into an amyloid 46 47 48 . This observation has pushed the development of over twenty different algorithms, aimed to identify these sequence stretches in disease-linked polypeptides 49 50 , whose predictions have been experimentally validated in many instances. Indeed, compounds blocking these regions have been shown to successfully interfere with entire protein aggregation reactions 51 and conversely mutations that increase the amyloid propensity of these stretches usually exacerbate full-length protein deposition 52 .…”
Section: Discussionmentioning
confidence: 99%
“…We describe the aggregating properties of proteins considering such the aggregation values as Spos, Sneg and Sall (see Material and methods ) for each amino acid residue along the protein sequence using the FoldAmyloid program [ 28 , 29 ]. Comparison of the results for 30 proteins [ 30 ] using eight different methods demonstrated that our method is among the best ones (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These Aggregation Prone Regions (APRs), also known as "hot spots", are generally composed of 5-15 amino acids, enriched in hydrophobic residues and with a low net charge. A number of computational methods have been developed in recent times to identify the presence of APRs in protein sequences, as a mean to predict a polypeptide's aggregation propensity (Castillo et al, 2011;Dovidchenko and Galzitskaya, 2015). Although these predictive methods rely on different assumptions and exploit different protein properties, they tend to provide consistent predictions and APRs can now be predicted with a high accuracy.…”
Section: Discussionmentioning
confidence: 99%